Mapping dysphagia in pediatric dystonia. - Muserrefe Nur Keles; Esra Serdaroglu (PLoS ONE)
Objectives Dystonia is a significant movement disorder in childhood, yet swallowing functions in this population remain largely unexplored. Dysphagia, however, can result in severe complications, including aspiration, underscoring the critical need for research in this area. This study, therefore, aimed to evaluate dysphagia in children with dystonia. Methods Children diagnosed with dystonia as the predominant movement disorder were included. Medical histories were recorded, and Gross Motor Function Classification System (GMFCS) and Functional Oral Intake Scale (FOIS) levels were determined. Oral structure characteristics were assessed, and chewing performance was evaluated using the Turkish version of Mastication Observation and Evaluation (T-MOE) and the Karaduman Chewing Performance Scale (KCPS). Swallowing safety was screened with the Pediatric Eating Assessment Tool-10 (PEDI-EAT-10) and the 3-ounce Water Swallow Test. The Dysphagia Disorders Survey (DDS) was used to assess swallowing disorder severity, while the Dysphagia Management Staging Scale (DMSS) was applied to determine the severity level of dysphagia. Results Twenty-five children (mean age: 11.32 ± 3.95 years) participated in the study. Of these 56% were classified as level V according to the GMFCS. Three children (12%) had a FOIS level of 4 or below. The mean T-MOE score was 15.62 ± 7.51, and 60% of the children could bite but could not chew effectively according to the KCPS. Oropharyngeal dysphagia was present in all children, with abnormal swallowing (PEDI-EAT-10 score ≥4) and increased aspiration risk (PEDI-EAT-10 score ≥13) observed in 100% and 88% of the participants, respectively. Additionally, 52.0% of the children failed the 3-ounce Water Swallow Test. The mean DDS raw score was 23.08 ± 7.70, and 68% of the children were classified as having severe or profound dysphagia based on the DMSS. Conclusion Swallowing dysfunction was observed in almost all children with dystonia, with the majority presenting with severe dysphagia and an elevated risk of aspiration. Close monitoring of oral structures and functions, along with continuous evaluation of swallowing performance, is crucial to ensure safe oral feeding and to mitigate life-threatening complications in this population.